The knowledge, attitude and practice of research misconduct among health sciences undergraduates: how do they associate? / Mohd Sham Othman ... [et al.] - Othman, Mohd Sham; Mat Ludin, Arimi Fitri; Muralitharan, Raveena Vaidheswaary; Wan Mohd Yaacob, Wan Muhamad Nasrul Naqim; Sze, Ling Liew; Zuha, Anis Afiqah; Ra'oh, Nur Amalia; Ahmad Ruzaini, Nur Raihan; Norazmi, Nur Amanina (Universiti Teknologi MARA, Perlis, 2022)
Research misconduct is an act of falsification, fabrication and plagiarism. This unethical act affects the quality of research publication among private and public sector and is a threat towards the public trust. Studies have shown that there are many factors contributing to the act of committing this behaviour such as environment, pressure and time constrain. Therefore, this study aims to determine the association between knowledge, attitude, and practice of research misconduct among undergraduate students of the Faculty of Health Sciences, Universiti Kebangsaan Malaysia. A questionnaire was adapted and modified for this study from the "Reporting of Suspected Research Misconduct in Biomedical and Behavioural Research" by the US Department of Health and Human Services, Office of Research Integrity. Universal sampling method was applied, and the participants were the 4th and 3rd year students. Quantitative cross-sectional study was employed for this study. As a conclusion, there is a weak association between the knowledge and attitude towards practices in research misconduct among undergraduate researchers of FSK, UKM KL which is not statistically significant.